Overweight and Obesity in Ahmedabad school going children: Magnitude in relationship to hypertension and associated risk factors - Arora, Bhoomi; Patel, Snehal (Indian Journal of Pharmacy Practice)
Introduction: India is undergoing a rapid epidemiological transition with increased urbanization and socio-economic development which has resulted in a dramatic change in lifestyle, consisting of physical inactivity, diet rich in fat, sugar and salt coupled with a high level of mental stress. Obesity is one of the most common diseases worldwide and the prevalence in school aged children appears to be increasing. Thus, the present study was planned to establish an association between body mass index (BMI) with hypertension and associated risk factors amongst school children in the age group of 12 to 17 years belonging to all socioeconomic group in Ahmedabad. Materials and Methods: A population based cross sectional study was conducted in the four schools of Ahmedabad. Using stratified random sampling method, 373 participants were selected. Body Mass Index (BMI) status and Blood Pressure (BP) were estimated using standard protocol and their various correlates regarding socio-demographic characteristics were looked into. Result: Prevalence of overweight and obesity was found to be 8.8% and 2.9% respectively. Prevalence of overweight and obesity was more prevalent among girls comparatively among boys. Overall prevalence of hypertension was 5.8%.The prevalence of obesity among students was higher in upper and upper middle socioeconomic class as compared to middle and low socioeconomic class. Family history of diabetes and obesity were also found to be positively associated. Conclusion: Childhood obesity and hypertension were found to be common in the city of Ahmedabad which suggest the need for greater public awareness programs on these morbidities.
Keywords: Overweight; Obesity; Children; Hypertension; Diet type; socioeconomic group